Household choice of water supply systems - Anand N. Asthana (1997)
Studies of pipe-water demand in developing countries have traditionally analysed household connection decisions to the pipe water system. These studies have yielded useful insights on the value of water and savings in time (e.g., Altaf et al., 1992; Asthana, 1995, 1996, 1997; Singh et al., 1993). Empirical observations, in some places, however, reveal that often households augment piped water supply with alternate sources. Households invest in coping strategies in the form of alternative supplies and storage facilities. Because these strategies have important implications, there is a need to develop an understanding of households’ water demand that goes beyond connection decisions. On the basis of theoretical advances made by BenAkiva, and Lerman, (1985) and their application by Madanat, and Humplick (1993), this paper presents a model system of household water supply choices. The model accounts for the possibility that the households may use different supply systems for different uses of water. Moreover, the relation between the households’ choice of water supply and their connection decisions is explicitly modelled.